111k views
3 votes
HELP ASAP

AND IF YOU COULD EXPLAIN, THATD BE GREAT​

HELP ASAP AND IF YOU COULD EXPLAIN, THATD BE GREAT​-example-1
User Granaker
by
5.3k points

1 Answer

2 votes

Answer:

-41

Explanation:

the problem is basically saying that we need to first substitute 5 in for x in the f(x) function first.

then we need to take that answer that we got and substitute it for x in the g(x) function.

i will do this step by step for you

start with the f(x) function

f(x) = 4x + 3

substitute 5 in for x

f(x) = 4(5) + 3

solve

f(x) = 20 + 3

f(x) = 23

now we use our answer from the f(x) function we just solved, and we put it into the g(x) function.

basically you are going to now substitute 23 for x in the g(x) function.

i will also do this step by step for you.

take the g(x) function

g(x) = -2x + 5

substitute 23 for x

g(x) = -2(23) + 5

solve

g(x) = -46 + 5

g(x) = -41

so now your overall answer is -41.

hope this helped!!!! good luck <3

User Keltex
by
5.2k points